INTERDISCIPLINARY DIMENSION OF CRITICAL INFRASTRUCTURE: FROM CLASSICAL TREATMENT TO COMPREHENSIVE MODEL - ZATONATSKIY, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Over the past decades, scientific and political discourse has increasingly focused on the issue of critical infrastructure (CI), which is considered a system-forming factor of stability, economic sustainability, and national security. The article offers an interdisciplinary overview of the evolution of the definition of "critical infrastructure" - from the classical, predominantly material-object interpretation to a comprehensive model that integrates physical and cyber components, social and cultural-symbolic dimensions. Based on a comparison of the approaches of the USA, EU, Great Britain, Japan and the PRC, it is shown how security priorities, institutional frameworks and historical experience shape different criteria for identifying and prioritizing CI sectors. The growing role of system-network methodologies for modeling interdependencies and cascading failures, as well as the need for an integrated paradigm of physical protection and cyber resilience, is substantiated. The Ukrainian context is presented through the prism of the Russian Federation's military aggression and the European integration course: the Law of Ukraine "On Critical Infrastructure" dated 11/16/2021 No. 1882-IX is analyzed, the shift in emphasis from a narrow defense and energy perspective to a risk-oriented, functional and socially motivated approach is highlighted. It is proven that the war became a catalyst for reviewing international practices and demonstrated the need to expand the list of critical sectors and synchronize risk management at the intersection of state policy, market and technology. The practical significance of the study lies in the formation of a two-layer (narrow and broad) definition of "critical infrastructure" and in developing recommendations for combining a clear classification of sectors, risk reduction tools and effective coordination of stakeholders in order to increase the overall stability of the system and strengthen economic security.
Keywords: infrastructure; critical infrastructure; cyber resilience; physical protection; cyber defense; economic security; military threats; European integration